Nonpharmacological Interventions for the Treatment of Cardiometabolic Risk Factors in People With Schizophrenia—A Systematic Review - Ewa Tumiel; Adam Wichniak; Marek Jarema; Michał Lew-Starowicz; Michał Lew-Starowicz (Frontiers in Psychiatry, 2019)
Background: People suffering from schizophrenia are notably vulnerable to cardiometabolic risk factors (CMRF), such as obesity, high blood pressure, hyperglycemia and insulin resistance, high serum triglycerides, and low serum high-density lipoprotein (HDL), which are related to increased mortality and decreased quality of life. The increased risk of “metabolic syndrome” (MS) is related to low physical activity, an unhealthy diet, and side effects of antipsychotic drugs. Nonpharmacological interventions seem to be important in the prevention and therapy of MS.Aim: This paper provides an overview of published studies and a critical analysis of pilot programs involving nonpharmacological measures aimed at prevention and treatment of CMRF in patients with schizophrenia.Material and Method: We searched the PubMed, PsycARTICLES, and Cochrane Library databases to identify clinical trials. We included full-text studies that met the following criteria: age > 18 years, a diagnosis of schizophrenia or schizoaffective disorder, and monitored parameters associated with MS.Results: All 1,555 references were evaluated for inclusion in the review, and 20 met the inclusion criteria. Nonpharmacological interventions led to improvement in physical health and showed a promising potential for implementation in treatment programs dedicated to this particular group of patients. However, a critical analysis revealed limitations, which have implications for the direction of future research.Conclusions: Patients suffering from schizophrenia can benefit from nonpharmacological interventions aimed at counteracting CMRF, improving either metabolic parameters, cardiovascular fitness, or their health perception. Notwithstanding, to achieve long-term effects, future studies should comprise appropriate follow-up procedures.